The World Outlook of the Renaissance and G. Vico’s Philosophy of History - Poviliūnas, Arūnas (Problemos, 1987)
An attempt is made to reveal the importance of the anthropocentric structure of being to the rise of the philosophy of history in the Renaissance. G. Vico’s “Scienza nuova” is chosen as an object of analysis. Self-consciousness of the Renaissance personality interpreted as creator of human universe is considered to be one of the important foundations of “Scienza nuova”. The author of the article maintains that “Eternal ideal history” transforms the instability of the artistic human individual treated as the principle of the cultural building into the constant mode of his existence.